Single-Strand Conformation Polymorphism Fingerprint Method for Dictyostelids - Pasookhush, Phongthana; Usmani, Asmatullah; Suwannahong, Kowit; Palittapongarnpim, Prasit; Rukseree, Kamolchanok; Ariyachaokun, Kanchiyaphat; Buates, Sureemas; Siripattanapipong, Suradej; Ajawatanawong, Pravech (Frontiers in Microbiology, 2021)
Dictyostelid social amoebae are a highly diverse group of eukaryotic soil microbes that are valuable resources for biological research. Genetic diversity study of these organisms solely relies on molecular phylogenetic of the SSU rDNA gene, which is not ideal for large scale genetic diversity study. Here, we designed a set of SSCP-PCR primers and optimized the SSCP fingerprint method for the screening of dictyostelids. The optimized SSCP condition required gel purification of the SSCP amplicons followed by electrophoresis using 9% polyacrylamide gel under 4ºC. We also tested the optimized SSCP procedure with 73 Thai isolates of dictyostelid that had the SSU rDNA gene sequences published. The SSCP fingerprint patterns were related to the genus-level taxonomy of dictyostelids, but the dendrogram did not reflect the deep phylogeny. This method is rapid, cost-effective, and suitable for massive sample screening compared to the phylogenetic analysis of the SSU rDNA gene sequences.